A novel arthroscopic all-inside suture technique using the Fast-Fix 360 system for repairing horizontal meniscal tears in young athletes: 3 case reports. Issue 7 (February 2018) - Atsumi, Satoru; Hara, Kunio; Arai, Yuji; Yamada, Manabu; Mizoshiri, Naoki; Kamitani, Aguri; Kubo, Toshikazu
Abstract: Rationale: Considering the risk of osteoarthritis following resection of a horizontally torn meniscus of the knee, repairing and preserving the meniscus as much as possible is preferred. We report 3 cases of restoration of horizontally torn menisci using a novel arthroscopic method we have called "all-inside interleaf vertical suture" that afforded preservation. Patient concerns: The 3 patients (aged 14, 17, and 21 years) had knee pain through sports activity. Diagnoses: All patients had horizontal tears in the posteromedial part of the meniscus. Interventions: The method uses Fast-Fix, whereby a first anchor is inserted from the tibial surface of the tear's superior leaflet and a second anchor is inserted from the femoral surface of the tear's inferior leaflet, and the 2 leaflets are closed using vertical suture. In all cases, the suture knots were embedded between the superior leaflet and inferior leaflet, avoiding contact with the articular cartilage, and superior leaflet and inferior leaflet crimping was good. Outcomes: All 3 were able to resume competing in sport and ≥ 1 year after surgery they had no pain and their postoperative mean Lysholm scores were 99.7. There were no complications or recurrence. On magnetic resonance imaging, the signal intensity of all the horizontal tears was high before surgery but low after surgery, suggesting that the repaired tear was healing. Lessons: The all-inside interleaf vertical suture procedure is a new surgical technique that can repair posteromedial horizontal meniscal tears of the knee of young people by easy crimping of the superior and inferior leaflets without the suture knots causing complications.